Are there benefits of culture-based detection of Mycobacterium avium spp paratuberculosis over histopathology? - Motlatso T. Hlokwe; Nomawethu S. Masina; Boitumelo Letsoko; Sewellyn C. Davey; Anita L. Michel (Onderstepoort Journal of Veterinary Research)
Paratuberculosis (Johne’s disease) has devastating outcomes on ruminant health and impacts on national and international trade. The current work assessed the diagnostic value of the VersaTREK automated liquid culture system in isolating Mycobacterium avium subspecies paratuberculosis (MAP) from faecal and intestinal tissue samples from ovine under South African conditions and compared it with the current method of choice, histopathological examination. Intestinal tissue and faecal samples from 111 sheep (including complete set from 104 slaughter sheep from flocks with a history of MAP infection as well as incomplete sample sets from 7 sheep) were analysed using the liquid culture method. One set of tissues was subjected to histopathological examination. Deoxyribonucleic acid (DNA) extracted from culture isolates was subjected to polymerase chain reaction (PCR) amplification using primers that target the IS900 regions of the MAP for species verification. Overall, the VersaTREK automated liquid culture in combination with IS900 PCR showed a comparable level of detection in tissues (12.6%) as histopathology (13.5%), but the detection rate for faecal samples was lower than for tissues (10.8%). A combination of histopathology and faecal culture increased the detection rate from 13.5% (n = 14/104) and 9.6% (n = 10/104), respectively, to 15.4% (n = 16/104).